2001
DOI: 10.1021/jo015632y
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Dichloro-9-thiabicyclo[3.3.1]nonane:  A Privileged, Bivalent Scaffold for the Display of Nucleophilic Components

Abstract: The title compound, the condensation product of sulfur dichloride and 1,5-cyclooctadiene, is a reliable acceptor of a wide variety of heteroatom nucleophiles, sometimes in reversible fashion. Optical resolution of the core structure has been achieved and preserved in succeeding transformations. The high reactivity and reliable stereochemical control afforded by this system illustrates the power of neighboring-group participation by the sulfur center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…It is known that a halogen atom is strongly activated in 2-haloethyl sulfides and selenides due to the anchimeric assistance effect with participation of sulfur or selenium atoms [25][26][27][28]. Nucleophilic substitution of halogen atoms in such compounds proceeds easily with a variety of nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that a halogen atom is strongly activated in 2-haloethyl sulfides and selenides due to the anchimeric assistance effect with participation of sulfur or selenium atoms [25][26][27][28]. Nucleophilic substitution of halogen atoms in such compounds proceeds easily with a variety of nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…[61] Structures with as many as 15 azobenzene moieties were prepared by iterative CuAAC/ S N 2 reactions (Scheme 15), taking advantage of the special anchimeric assistance reactivity of b-haloamine electrophiles with azide. [62] It was shown that, despite the steric hindrance within the dendrimer structure, all of the azobenzene groups could quantitatively be converted between cis and trans isomers reversibly using UV and visible light, respectively. The authors mention the potential of these dendrimers as fast, nanoscale, photoactive switches.…”
Section: Methodsmentioning
confidence: 99%
“…The driving force for the rearrangement may be due to anchimeric assistance, [29][30][31] which causes high mobility of the bromine atom. This effect is important for the stabilization of cation 4, the assumed intermediate.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The halogen atom in 2-haloethyl sulfides and selenides is known to be strongly activated by the anchimeric assistance effect with participation of the sulfur or selenium atom. [29][30][31] Replacement of halogen atoms by a nucleophile in 2-haloethyl sulfides and selenides proceeds exceptionally easily. The formation of 3-membered thiirane and selenirane intermediates has been suggested to explain the considerable increase of the rate in nucleophilic substitution reactions.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%